PENGENDALIAN KUALITAS PROSES PRODUKSI KEMEJA DENGAN METODE FAULT TREE ANALYSIS (FTA) DAN FAILURE MODE AND EFFECT ANALYSIS (FMEA) DI CV.ABC - Rahmi Dwi Fitriani (2022)
CV. ABC is a company engaged in the convection industry. Based on company data for January 2022-March 2022, shirt production has the highest number of defects, which is 147 pcs. Therefore, quality control is needed in the shirt production process at CV. ABC and quality control are carried out using FTA and FMEA methods. The results showed that the dominant defect in the shirt product was CV. ABC is the defect of the emblem not being centered, the defect of the reverse embroidery, and the defect of the sleeve not being buttoned. Then an FTA analysis is carried out to determine the factors causing the defect. The causative factors consist of a method, man, environment, and materials. Several improvement plans are given to reduce the number of defects, namely conducting regular training to production operators, conducting briefings before starting work, providing education to operators, and adding a short break schedule to the work schedule. Then a multiple linear regression model was conducted to determine the contribution of the factors causing defects to the resulting product defects.